Effect of Superstructure Materials and Misfit on Stress Distribution in a Single Implant-Supported Prosthesis: A Finite Element Analysis - Assunção, Wirley Goncalves [UNESP]; Gomes, Erica Alves [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Delben, Juliana Aparecida [UNESP]; Tabata, Lucas Fernando [UNESP]; Sousa, Edson Antonio Capello [UNESP] (Lippincott Williams & Wilkins, 2010)
This finite element analysis study evaluated the optimal material combination for the superstructure of single implant-supported prosthesis with different fit patterns. Two models of a two-dimensional finite element analysis were constructed: group A (control), prosthesis presenting precise fit to implant; and group B, prostheses with unilateral angular misfit of 100 Km. Each group was divided into 5 subgroups according to different materials for framework (gold alloy, titanium, and zirconia) and veneering (porcelain and modified composite resin). Evaluation was performed on ANSYS software with 133-N load applied at the opposite side of misfit on the model. The load was applied with a 30-degree angulation and 2-mm off-axis. The presence of unilateral angular misfit (group B) increased the von Mises stresses in the implant (40%) and retention screw (7%) in comparison to group A. The combination of porcelain/titanium and porcelain/zirconia displayed more favorable stress distribution. When gold alloy was used as a framework material, there was no difference in stress values for both veneering materials in all groups. The use of stiffer and softer superstructures materials did not affect the stress distribution and stress values in the supporting tissue. According to the biomechanical point of view, materials with high elasticity modulus are more suitable for the superstructure of implant-supported prosthesis.
Keywords: Prosthesis; dental implants; misfit; superstructure materials; finite element analysis